How does the fire regime change after creating a protected area in the Brazilian Cerrado? - de Carvalho, Izadora S.; Alvarado, Swanni T.; Sanna Freire Silva, Thiago; Leandro de Oliveira Cordeiro, Carlos; Fidelis, Alessandra [UNESP]; Valéria Carvalho Saraiva, Raysa; A.M.M.A. Figueiredo, Fábio; Roberto P. de Sousa, José; Massi Ferraz, Tiago (Elsevier, 2023)
Fire is a natural factor maintaining biodiversity and several ecological processes. The Brazilian Cerrado, considered the savanna with the highest biodiversity, is characterized by climatic seasonality, vegetation mosaics and topographic variations that together with fire determine its different plant physiognomies. The Chapada das Mesas National Park (CMNP), located in the south of the state of Maranhão (Brazil), has different savanna plant physiognomies with high ecological potential and archaeological and water wealth. The aim of the present study was to reconstruct the fire history over 28 years for the park and its surroundings (20 km buffer area), endeavouring to understand the impact of the creation of this National Park on its fire regime. Landsat satellite images were used from the TM, ETM + and OLI sensors to map the fire scars, which were identified and vectorized manually. The database created was used to analyze the total annual burned area, burned area percentage, density ignition, mean burn scar area and fire frequency during the mapped period. In total, 86 % of the CMNP was burn at least once between 1990 and 2017, while 72 % of the buffer area was burn. The creation of the park had significant effects on the density ignition when the periods before (1990–2005) and after (2006–2017) its creation were compared, and showed no significant effects on total annual area burned and average burn scar area. Despite the amount of burned area over time did not change significantly between the years before and after, the main change was observed in the fire seasonality after the creation of the park. In the park, 38 % of the area had a frequency of burn areas higher than ten times in the 28-year interval while 13 % of the buffer area was burn more than 10 times. In contrast, 23 % and 15 % had a fire frequency of 2 to 4 times on the buffer and the park respectively. Although the park was created to mitigate the human impacts of fire, the geographic isolation, the current occupation of the park by local populations and the pressure from agricultural expansion in the surroundings are influencing these conservation measures. Understanding the spatial–temporal distribution of fire in protected areas of the Cerrado contributes to improving management, preservation and conservation actions, so that in future studies other factors can be included to better understand the dynamic of fire occurrence in the region of the CMNP and in other protected areas of the Cerrado.
Keywords: Burned area; Fire frequency; Fire season; Land use change; Protected areas management